A Log-Based Analysis of the Associations Between Creativity and Computational Thinking. (September 2021) - Israel-Fishelson, Rotem; Hershkovitz, Arnon; Eguíluz, Andoni; Garaizar, Pablo; Guenaga, Mariluz
Creativity and Computational Thinking (CT) have been both extensively researched in recent years. However, the associations between them are still not fully understood despite their recognition as essential competencies for the digital age. This study looks to bridge this gap by examining the association between CT and two types of creativity, i.e., Creative Thinking and Computational Creativity. The research was conducted among 124 middle school students from Spain, who were divided into control and experimental groups; the intervention included an explicit encouragement to be as creative as possible (i.e., to submit multiple correct solutions) in a given learning task. Data were analyzed from a standardized creativity test (Torrance's TTCT) and cross-referenced with log files that documented the students' activities in the Kodetu game-based learning environment. Our research findings indicate some interesting associations between CT and Creativity. First, we found that creativity contributes to CT. Second, we found that CT is transferable across different domains. Finally, we found that Computational Creativity can develop and improve over time.